Anxiety-Induced Sleep Disturbance and Associated Lifestyle Behaviors According to Sex in Argentine Adolescents - López-Gil, José Francisco; Cavero-Redondo, Iván; Tárraga López, Pedro J.; Jiménez-López, Estela; González, Alberto Durán; Sequí-Domínguez, Irene; Mesas, Arthur Eumann (Frontiers in Behavioral Neuroscience, 2022)
Purpose: The aim of the current study was twofold: first, to determine the prevalence of anxiety-induced sleep disturbances among Argentine adolescents according to sex, and second, to identify the association between these sleep disturbances and lifestyle behaviors in this population. Methods: This is a cross-sectional study with data from the Global School-based Student Health Survey (GSHS) in Argentina (2018). A total of 32,393 adolescents (aged 12 to 17 years; 53.4% girls) were included in the final analysis. Anxiety-induced sleep disturbances were assessed with the question “During the past 12 months, how often have you been so worried about something that you could not sleep at night?”. Results: The prevalence of anxiety-induced sleep disturbances was higher in girls (17.4%) than in boys (7.9%) (p<0.001). In boys, results indicated that those who used marijuana (cannabis) (odds ratio [OR]=1.46, 95% confidence interval [CI] 1.08–1.98), used amphetamine or methamphetamine (OR=2.19, 95%CI 1.28–3.77), walked or biked to or from school (OR=1.53, 95%CI 1.19–1.96), and spent 3 hours or more in sedentary behaviors (OR=1.35, 95%CI 1.05–1.74) were more likely to report anxiety-induced sleep disturbances. In girls, those who ate from a fast-food restaurant (OR=1.24, 95%CI 1.05–1.47), consumed alcoholic beverages (OR=1.45, 95%CI 1.19–1.75), smoked cigarettes (OR=2.09, 95%CI 1.05–4.14), consumed any tobacco product (OR=1.47, 95%CI 1.19–1.82), used amphetamine or methamphetamine (OR=2.08, 95% CI 1.33–3.26), and those who spent 3 hours or more in sedentary behaviors (OR=1.32, 95%CI 1.11–1.57) were more likely to report frequent anxiety-induced sleep disturbances. Conclusion: In conclusion, considerable sex differences were observed with respect to the prevalence of anxiety-related sleep disturbances and associated lifestyle aspects.